Efek intervensi permen probiotik Lactobacillus plantarum Dad-13 terhadap kualitas feses dan komposisi mikrobia usus balita gizi kurang - Rafli Zulfa Kamil; Agnes Murdiati; Mohammad Juffrie; Endang Sutriswati Rahayu (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Undernutrition, a high nutritional problem in Indonesia, can be caused by the imbalance of the gut microbiota composition and gut healthiness. Probiotic intervention is one of the ways that can maintain those aspects. Preventive steps to address malnutrition can improve human resources in the future.Objectives: This research aimed to evaluate the efficacy of probiotic L. plantarum Dad-13 intervention on fecal quality and gut microbiota modulation of undernourished infants. Methods: This research was conducted in Tirtoadi Village, Sleman, Yogyakarta, from January to March 2020, using a randomized, double-blind clinical control trial design with two groups: placebo (n:15) and probiotic (n:15), over a 50-day intervention period. The probiotic group was given L. plantarum Dad-13 candy, while the placebo group was given candy with the same composition but without adding L. plantarum Dad-13. Anthropometric measurements and feces sampling were carried out before and after the intervention. Fecal samples were then analyzed for fecal quality and intestinal microbial composition. The data obtained were analyzed using the Wilcoxon paired test for within-group differences (before and after the intervention). In contrast, the Wilcoxon rank-sum test was used for between-group analysis (placebo and probiotic).Results: The result showed that the intervention of L. plantarum Dad-13 candy improved defecation frequency (p<0,024) and fecal consistency towards the normal category.  Besides that, although there is no change in the F/B ratio, L. plantarum Dad-13 intervention also enhanced the number of genus-related Firmicutes phylum, which have the benefit of maintaining gut health and inhibiting the growth of pathogenic bacteria.Conclusion: Therefore, probiotic L. plantarum Dad-13 can prevent the progression of stunting in undernourished children.